RISK MANAGEMENT IN NGBC PLANT USING HAZARD IDENTIFICATION RISK ASSESSMENT AND RISK CONTROL (HIRARC) AT PT XYZ - Aditya, Falah Dwi; Febriansyah, Indra; Subagja, Kurnia Robbi; Sipahutar, Nova Putri; Maskur, Rohmatikal; Rahmana, Arief (CENTRAL ASIA AND THE CAUCASUS, 2022)
PT XYZ is a company that produces fiber as the main product with capacity of220.000 tons per year. In this fiber production process, PT. XYZ uses several types of chemicals. One of them is carbon disulfide which is produced by the Natural Gas Based Carbon (NGBC) plant. Based on accident data from 2015 to 2021 at the NGBC plant, there were no work accidents that occurred in fatalities. PT XYZ wants to continue to improve working conditions by managing the hazards that exist in the work location. This goal is also in line with the company's vision to become an excellent company in safety and health, good for the planet and people, and exceed compliance to global and local regulations. This research was conducted using the Hazard Identification, Risk Assessment and Risk Control (HIRARC) method. HIRARC is a method that aiming to identify hazard, assess and control risk. From the process implementing hazard identification, there are 7 risks categorized as medium risk, 17 risks categorized as high risk and 3 risks categorized as extreme risk. The basic causes of the risk come from lack of awareness, lack of discipline, lack of interlock in some systems, insufficient rest breaks, repetitive awkward postures, and poor housekeeping.